Cusps and Distortions in Ionospheric FI-layer observed over Kodaikanal - SANKARAN, K. S. (MAUSAM, 1964)
A special study of cusps and distortions in F1-layertraces has been made from ionograms obtained at Kodaikanal during a period of about half a solar cycle. Two different types of disturbance have been noticed. The first one is stationary type occurring near the low frequency end of the F1-layer trace. It is suggested that these ridges found in the course of a disturbance are connected with the E2-layer. In the second type, the cusp appears to move along the virtual height curve and these are ascribed to traveling wave-type disturbance. It is also found that these disturbances are associated with the disappearance of equatorial E8 on magnetically disturbed days, An explanation of the phenomenon is attempted in terms of internal gravity waves proposed by Hines (1960).